Using Constant Time Delay to Teach Braille Word Recognition. (March 2014) - Hooper, Jonathan; Ivy, Sarah; Hatton, Deborah
Introduction: Constant time delay has been identified as an evidence-based practice to teach print sight words and picture recognition (Browder, Ahlbrim-Delzell, Spooner, Mims, & Baker, 2009). For the study presented here, we tested the effectiveness of constant time delay to teach new braille words. Methods: A single-subject multiple baseline across behaviors design was used to investigate the use of constant time delay to teach recognition of highly motivating braille words to four students with visual impairments and intellectual disabilities. Results: Each participant learned all words taught (9–12 words each). A functional relation was demonstrated for all four participants by immediate changes in trend from baseline to intervention. Discussion: This is the first published report of the successful use of constant time delay to teach braille word recognition to students with visual impairments and intellectual disabilities. An attending cue was introduced into the procedures for students with a low number of unprompted correct responses, and results were positive. Possible sources of variability in word retention are discussed. Implications for practitioners: Results suggest constant time delay can be adapted and implemented with braille readers in typical teaching environments.